Identification of a Novel Ferroptosis-Related Gene Prognostic Signature in Bladder Cancer - Sun, Jiale; Yue, Wenchang; You, Jiawei; Wei, Xuedong; Huang, Yuhua; Ling, Zhixin; Hou, Jianquan (Frontiers in Oncology, 2021)
Background: Ferroptosis is a newly found nonapoptotic forms of cell death that plays an important role in tumors. However, the prognostic value of ferroptosis-related genes (FRG) in bladder cancer (BLCA) have not been well examined. Methods: FRG data and clinical information were collected from The Cancer Genome Atlas (TCGA). Then, significantly different FRGs were investigated by functional enrichment analyses. The prognostic FRG signature was identified by univariate cox regression and least absolute shrinkage and selection operator (LASSO) analysis, which was validated in TCGA cohort and Gene Expression Omnibus (GEO) cohort. Subsequently, the nomogram integrating risk scores and clinical parameters were established and evaluated. Additionally, Gene Set Enrichment Analyses (GSEA) was performed to explore the potential molecular mechanisms underlying our prognostic FRG signature. Finally, the expression of three key FRGs were verified in clinical specimens. Results: 32 significantly different FRGs were identified from TCGA-BLCA cohort. Enrichment analyses showed these genes were mainly related to the ferroptosis. 7 genes (TFRC, G6PD, SLC38A1, ZEB1, SCD, SRC and PRDX6) were then identified to develop a prognostic signature. The Kaplan–Meier analysis confirmed the predictive value of the signature for overall survival (OS) in both TCGA and GEO cohort. A nomogram integrating age and risk scores was established and demonstrated high predictive accuracy, which was validated through calibration curves and receiver operating characteristic (ROC) curve (AUC=0.690). GSEA showed that molecular alteration in the high-risk group or low-risk group was closely associated with ferroptosis. Finally, experimental results confirmed the expression of SCD, SRC and PRDX6 in BLCA. Conclusion: Herein, we identified a novel FRG prognostic signature that may involve in BLCA. It showed high values in predicting OS and targeting these FRGs may be an alternative for BLCA treatment. Further experimental studies are warranted to uncover the mechanisms that these FRGs mediate BLCA progression.